A powerful couple in the future of clinical biochemistry: in situ analysis of dried blood spots by ambient mass spectrometry. (November 2010) - Corso, Gaetano; D'Apolito, Oceania; Gelzo, Monica; Paglia, Giuseppe; Russo, Antonio Dello
Since the early 1960s, dried blood spots (DBS) on filter paper have been used in clinical applications. The first key milestone in the use of DBS was the screening of phenylketonuria and other inborn errors of metabolism using microbiological and enzymatic analytical methods. 20 years after its introduction, advanced mass spectrometers and new soft ionization techniques have permitted the coupling of liquid chromatography with MS and tandem MS (MS/MS) and since the 1990s, DBS analysis by LC–MS/MS expanded screening to many inborn errors of metabolism simultaneously. Recently, DBS–LC–MS/MS analysis has been used in other fields such as pharmacology, toxicology and forensic sciences. Today, new ambient ionization techniques, coupled to MS, directly desorb/ionize molecules from solid samples. This presents new opportunities for the in situ analysis of DBS. Most likely, ambient MS methods will be used to analyze DBS, increasing the clinical applications of MS within the next 10 years.